Review Article: Role of FeoA in the Interaction with the Fe2+-Fur Complex in E. coli: Ulasan Artikel: Peran FeoA dalam Interaksi dengan Kompleks Fe2+-Bulu Kompleks dalam E. coli - Alali, Sheama (Academia Open, 2024)
Iron is an essential micronutrient for bacteria, functioning as a cofactor in vital processes such as electron transport, heme synthesis, and DNA replication. However, excess iron triggers the Fenton reaction, producing harmful reactive oxygen species. To manage this, E. coli has evolved regulatory systems to maintain iron balance despite its scarcity in the environment, with free iron concentrations as low as 10^-18 M. The iron-binding repressor protein Fur regulates genes involved in iron uptake, transfer, and storage. The FeoABC system is the primary route for Fe2+ entry, with FeoB enabling the reduction of Fe3+ to Fe2+ and transferring it to FeoA, which likely prevents wasteful iron binding to negatively charged cellular membranes. This efficient management of iron acquisition and storage not only ensures cellular survival but also provides insights into bacterial metabolic strategies for optimizing iron use while minimizing damage from reactive oxygen species. Highlights: Iron is crucial for bacterial functions like DNA replication and heme synthesis. Excess iron triggers Fenton reaction, creating harmful reactive oxygen species. FeoABC system regulates Fe2+ uptake and balances iron acquisition in bacteria. Keywords: Iron homeostasis, FeoABC system, E. coli, Fur protein, reactive oxygen species